Anti-racist Shakespeare - Dadabhoy, Ambereen; Mehdizadeh, Nedda (Cambridge New York, NY Cambridge University Press, 2023)
Anti-Racist Shakespeare argues that Shakespeare is a productive site to cultivate an anti-racist pedagogy. Our study outlines the necessary theoretical foundations for educators to develop a critical understanding of the longue durée of racial formation so that they can implement anti-racist pedagogical strategies and interventions in their classrooms. This Element advances teaching Shakespeare through race and anti-racism in order to expose students to the unequal structures of power and domination that are systemically reproduced within society, culture, academic disciplines, and classrooms. We contend that this approach to teaching Shakespeare and race empowers students not only to see these paradigms but also to take action by challenging and overturning them. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 19 Jan 2023).
Keywords: Shakespeare, William -- 1564-1616 -- Study and teaching; Critical race theory; Anti-racism -- Study and teaching